Pengukuran Kualitas Pendidikan Kabupaten Sidoarjo pada Jenjang SMP dengan Structural Equation Modeling - Fitriani, Fenny; Pramesti, Wara; Anuraga, Gangga (UJMC (Unisda Journal of Mathematics and Computer Science), 2024)
The better the quality of education in a country, it can be considered that the quality of human resources in the country is qualified and can be a good development support for the country. However, there is a gap in education in Indonesia. This gap also occurs at a more regional scope such as districts/cities. One of the districts/cities experiencing education gaps is Sidoarjo district. This gap is thought to be influenced by differences in the factors that shape the quality of education in each school. Therefore, it is necessary to study how much influence each factor has on the quality of education. This article explores the quality of education in Sidoarjo district using structural equation modeling (SEM) at the junior high school level. The use of SEM is based on its ability to analyze two or more variables that cannot be measured directly. From the results of the analysis, it was found that infrastructure and socioeconomic factors have a significant effect on education quality. Infrastructure factors have a greater effect on the quality of education when compared to socioeconomic factors